Effect of haemodialysis on the pharmacokinetics and pharmacodynamics of evogliptin - Kim, Byungwook; Im, Dha Woon; Won, Heejae; Sunwoo, Jung; Han, Seung Seok; Lee, Hajeong; Kim, Dong Ki; Oh, Kook‐Hwan; Joo, Kwon Wook; Kim, Yon Su; Cho, Joo‐Youn; Lee, SeungHwan; et al. (Diabetes, obesity & metabolism, 2023)
Aim To investigate the possible effect of haemodialysis (HD) on the pharmacokinetic (PK) and pharmacodynamic (PD) characteristics of evogliptin, a dipeptidyl peptidase‐4 (DPP‐4) inhibitor. Methods A single‐dose, open‐label, parallel‐group study of eight end‐stage renal disease (ESRD) patients and eight matched healthy subjects was conducted. ESRD patients received a single oral dose of evogliptin 5 mg after and before HD with a 2‐week washout between each dose, and healthy subjects received a single oral dose of evogliptin 5 mg. Serial blood, dialysate, and urine samples were collected to assess the PK and PD profiles of evogliptin. To compare PK parameters before and after HD, geometric mean ratios (GMRs) and 90% confidence intervals (CIs) were calculated. Results The GMRs for the maximum concentration and area under the concentration‐time curve from time 0 to the last measurable timepoint (AUClast) of evogliptin when administered before HD compared with after HD were 0.7293 (90% CI 0.6171‐0.8620) and 0.9480 (90% CI 0.8162‐1.1010), respectively. The maximum DPP‐4 inhibitory effect, area under the DPP‐4 inhibitory effect‐time curve, and time duration of more than 80% DPP‐4 inhibition were comparable when evogliptin was administered before and after HD. Compared with healthy subjects, the mean AUClast of evogliptin was approximately 1.4‐fold greater in ESRD patients, but the difference is unlikely to affect the safety and efficacy of evogliptin. Conclusion The effect of HD on the PK and PD characteristics of evogliptin was not clinically significant; therefore, dose adjustment according to HD status is not necessary.